Modelling, fabrication and experimental testing of an heat sink free wearable thermoelectric generator. (1st August 2017) - Francioso, L.; De Pascali, C.; Sglavo, V.; Grazioli, A.; Masieri, M.; Siciliano, P.
Highlights: Experimental investigation of a functional wearable thermoelectric generators without heat sink. Flexible thermoelectric generator for wearable and industrial applications. Thermal model optimization, simulation, and device fabrication of a PDMS based thermoelectric generator. Experimental demonstration of a flexible TEG coupled with a state-of-the art CMOS 65 nm DC-DC converter. Abstract: Thermoelectric pastes of stoichiometric Sb2 Te3 and Bi2 Te3 were prepared, characterized and used as active materials to fabricate a flexible heat sink free thermoelectric generator (TEG). The module was designed to be coupled to a 80 mV start-up input voltage fully electrical DC-DC converter. Although practical aspects and technological limitations led to a not optimal dimensioning of the device, an improvement of its thermoelectric performance might be obtained by including an additional thick film metal layer on the two sides of TEG, as demonstrated by Finite Element Analysis (FEA) results. The designed thermopile consists of 450 thermocouples realized by blade coating of p- and n-type materials into 2 mm tall vertical cavities of a pre-patterned Polydimethylsiloxane (PDMS) through-holes layer of total area 98 × 98 mm 2 . For a first functional investigation, a prototype of 45 thermocouples into a footprint area of about 2.2 × 10 −3 m 2 was fabricated and tested to evaluate its thermoelectric performance stand-alone and coupled with the DC-DC converter. A mean Seebeck coefficient of about 60 μV/K for pn couple was calculated from experimental data, and a power of about 27 nW was measured at 10 K on matched load of about 6.8 kΩ. A temperature difference of about 1.8 °C was achieved between the junctions in working conditions next to those typical of human body wearing in indoors (quiescent air at room temperature, constant temperature of 34.8 °C applied on the TEG hot side). The investigation shown that a thermopile of 450 couples requires a minimum thermal gradient of about 2 °C between junctions to be able to switch on the custom voltage boost DC-DC converter.